Enhancing access to primary care is critical to the future of an equitable health service: using process visualisation to understand the impact of national policy in the UK - Litchfield, Ian; Gale, Nicola Kay; Greenfield, Sheila; Shukla, David; Burrows, Micheal (Frontiers in Health Services, 2025)
Access to UK general practice is complicated by the need to provide equitable and universal care within a system adapting to workforce challenges, digital innovation, and unprecedented demand. Despite the importance of accessing primary care in meeting the overall aim of delivering equitable care, this is the first time the direct and indirect influence of policies intended to facilitate access have been systematically explored. Further consideration by policymakers is needed to accommodate the difference between what patients need and what patients want when accessing primary care, and the differences in their ability to utilise digital options. The designation of care was hindered by long-standing issues of reliable data and variations in the interpretation of local and national protocols and guidelines.